(untitled) (Literasi Nusantara, 2025)
Learning motivation has an important role in the learning process. To foster learning motivation, strategy that can be done is to use interactive media in learning. Baamboozle as one of the website-based learning media comes as an innovation from technological developments. This research discusses about how the use of Baamboozle has the potential to affect student learning motivation at the elementary school level. This research was conducted using a literature study approach, namely the process of reviewing various sources to obtain data related to the research objectives. The literature search was conducted using the publish or perish 8 application which then the results were analyzed qualitatively. Based on the analysis of 10 related articles, it was concluded that Baamboozle has a positive effect on students’ learning motivation seen from its role which is able to involve students during the learning process so as to create more fun and meaningful learning.